A Survey on Man in the Middle Attack: Classification, Defense Mechanisms and Challenges - Kalita, Manjula; Dutta, Sukanya; Yesmin, Ayesha (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a survey of man-in-the-middle attacks in communication networks and methods of protection against them. Man in the middle attack allows the attacker to gain unauthorized entry into the connection between two devices and listen to the network traffic. This paper focuses on the areas where man-in-the-middle attack can occur and the different methods with which we can defense against the attack.